The Influence of Law Enforcement, The Role of Parents in Tackling Juvenile Delinquency Concuming Drugs in Sukabumi District - Zulfikri Darwis (Westscience Press, 2023)
This study aimed to examine the influence of law enforcement and parental involvement on juvenile delinquency related to drug consumption in Sukabumi District, Indonesia. The study used a quantitative approach with a cross-sectional design, and data were collected through a survey of 300 young people aged 15 to 24 years. The results showed that 20% of young people reported using drugs in the past year, with marijuana being the most commonly used drug. Chi-square tests revealed a significant relationship between drug use behavior and the perception of the influence of law enforcement and parental involvement. Young people who reported using drugs were more likely to perceive law enforcement and parental involvement as not having a significant influence on their drug use behavior. The mean scores for the perceived influence of law enforcement and parental involvement on drug use behavior were moderate. Overall, the findings suggest that there is a need to improve the effectiveness of law enforcement and parental involvement in preventing juvenile delinquency related to drug consumption in Sukabumi District.